PENERAPAN SANKSI TERHADAP PELANGGARAN PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) OLEH PERSEROAN TERBATAS - Hidayat, Taufik; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
The purpose of establishing a company is to get maximum profit or profit. In addition to profit or profit, the company has an obligation to social and environmental responsibility (TJLS) or Corporate Social Responsibility (CSR) to the general public. Different interpretations of the company's TJLS implementation cause social conflict. Overlapping regulations and the absence of complete regulations on TJLS cause problems in the community. An example of social conflict is a class action lawsuit against 3 (three) C excavation mining companies in Palu City, Central Sulawesi, for not implementing TJSL. By examining the decision of the Palu District Court and the reconsideration decision of the class action lawsuit dispute to 3 (three) C excavation mining companies in Palu City, Central Sulawesi, the author will describe several problems regarding how law enforcement, the form of legal sanctions and the role of the government related to companies that do not implement TJLS to the community and the environment. The research method used is normative legal research using secondary data and analyzed descriptively. The results of this study are How is law enforcement and the form of legal sanctions related to companies that do not carry out social and environmental responsibility.Keywords: Corporate Social Responsibility